Butterfly dichromatism primarily evolved via Darwin's, not Wallace's, model. Issue 6 (23rd October 2020) - van der Bijl, Wouter; Zeuss, Dirk; Chazot, Nicolas; Tunström, Kalle; Wahlberg, Niklas; Wiklund, Christer; Fitzpatrick, John L.; Wheat, Christopher W.
Abstract: Sexual dimorphism is typically thought to result from sexual selection for elaborated male traits, as proposed by Darwin. However, natural selection could reduce expression of elaborated traits in females, as proposed by Wallace. Darwin and Wallace debated the origins of dichromatism in birds and butterflies, and although evidence in birds is roughly equal, if not in favor of Wallace's model, butterflies lack a similar scale of study. Here, we present a large‐scale comparative phylogenetic analysis of the evolution of butterfly coloration, using all European non‐hesperiid butterfly species ( n = 369). We modeled evolutionary changes in coloration for each species and sex along their phylogeny, thereby estimating the rate and direction of evolution in three‐dimensional color space using a novel implementation of phylogenetic ridge regression. We show that male coloration evolved faster than female coloration, especially in strongly dichromatic clades, with male contribution to changes in dichromatism roughly twice that of females. These patterns are consistent with a classic Darwinian model of dichromatism via sexual selection on male coloration, suggesting this model was the dominant driver of dichromatism in European butterflies.